Universality of quantum Brownian motion - Lutz, Eric; Weidenmüller, Hans-Arwed (Physica. A, Statistical mechanics and its applications, 1999)
Are Markovian master equations for quantum Brownian motion independent of model assumptions used in the derivation and, thus, universal? With the aim of answering this question, we use a random band-matrix model for the system-bath interaction to derive Markovian master equations for the time evolution of one-dimensional quantum systems weakly coupled to a heat bath. We study in detail two simple systems, the harmonic oscillator and the two-level system. Our results are in complete agreement with those of earlier models, like the Caldeira-Leggett model and, in the large-band limit, with the Agarwal equations (both with and without rotating-wave approximation). This proves the universality of these master equations.